2020
DOI: 10.1007/s00464-020-07920-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of first-line therapeutic interventions for achalasia: a systematic review and network meta-analysis

Abstract: Background Several interventions with variable efficacy are available as first-line therapy for patients with achalasia. We assessed the comparative efficacy of different strategies for management of achalasia, through a network meta-analysis combining direct and indirect treatment comparisons. Methods We identified six randomized controlled trials in adults with achalasia that compared the efficacy of pneumatic dilation (PD; n = 260), laparoscopic Heller myotomy (LHM; n = 309), and peroral endoscopic myotomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
(75 reference statements)
0
21
0
2
Order By: Relevance
“…Sanaka et al [29], compared geriatric (> 65 years) vs non-geriatrics (< 65 years) retrospectively, and they found no differences in success at 2 months (94.9 % vs 94.7 %; P = NS), and similar AE (10.1 % vs 3.8 %; P = 0.42), confirming good safety and efficacy. Chen et al [31], in an international multicenter retrospective study, evaluated 76 octogenarian patients and found at mid-term (265 days), a 93.4 % of clinical success, but up to 14.5 % AE, of whom 7.1 % were severe, confirming, that in spite of POEM being safe and effective in younger patients, serious AE could be presented in octogenarian population, being higher in LHM (AE = 3 %-19 %) for these patients [8][9][10]. Low-grade esophagitis was defined as grade A or B according to LA classification system [35] and it was presented in 4.7 % to 11.2 % of our patients during follow-up.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Sanaka et al [29], compared geriatric (> 65 years) vs non-geriatrics (< 65 years) retrospectively, and they found no differences in success at 2 months (94.9 % vs 94.7 %; P = NS), and similar AE (10.1 % vs 3.8 %; P = 0.42), confirming good safety and efficacy. Chen et al [31], in an international multicenter retrospective study, evaluated 76 octogenarian patients and found at mid-term (265 days), a 93.4 % of clinical success, but up to 14.5 % AE, of whom 7.1 % were severe, confirming, that in spite of POEM being safe and effective in younger patients, serious AE could be presented in octogenarian population, being higher in LHM (AE = 3 %-19 %) for these patients [8][9][10]. Low-grade esophagitis was defined as grade A or B according to LA classification system [35] and it was presented in 4.7 % to 11.2 % of our patients during follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…Second, BSP is performed in a conventional fluoroscopy ▶ Table 1 Characteristics of patients and procedures. and endoscopy suite, only deep sedation is needed, there is easy placement, and no removal is needed [18,[20][21][22], representing a promising alternative in octogenarian patients with a high-risk nature (comorbidity, esophageal mucosal fragility, and anatomic esophageal changes due to aging) [1,8,10,17]. Diameter use was based on previous studies with SEMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we considered the use of BSP, based on two reasons: first, because of its safety and efficacy observed in other gastrointestinal diseases, such as BES and small bowel strictures 17 . Second, BSP is performed in a conventional fluoroscopy and endoscopy suite, only deep sedation is needed, there is easy placement, and no removal is needed 18 20 21 22 , representing a promising alternative in octogenarian patients with a high-risk nature (comorbidity, esophageal mucosal fragility, and anatomic esophageal changes due to aging) 1 8 10 17 . Diameter use was based on previous studies with SEMS.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic Heller Myotomy (LHM) and Peroral endoscopic myotomy (POEM) are considered the gold standard of treatment 4 5 6 ; however, safety is compromised in some populations, such as in elderly patients (adverse events of 2 % to 11.5 % in LHM and 5 % to 7.8 % for POEM 7 8 9 ), representing high-risk procedures for them. Alternative treatments include pneumatic dilation (PD) (73 %–88 % early and mid-term efficacy, but a median of 1.9 % perforation rate 4 5 6 7 8 9 10 ) and botulinum toxin injection (BTI) (initial 87 % to 92 %, but 22 % to 31 % mid-term efficacy 8 11 ). Fully or partially covered self-expandable metal stents (SEMS) have been used with variable clinical remission rates (88 % to 100 % at early-term and 49 % to 91 % at long-term 12 13 ), but with concerning adverse events (AEs) (thoracic pain 35 % to 44 %, reflux symptoms 28 % to 36 %, migration 8.5 % to 18 %, and bleeding 8 % to 12 % 14 15 16 ).…”
Section: Introductionmentioning
confidence: 99%